2022
DOI: 10.6018/sportk.536581
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary global trends in choreographic art development at the beginning of the 21st century

Abstract: The aim of this study was to identify the main contemporary global trends of choreographic art at the beginning of the XXI century and illustrate the practical aspects of existing trends in world choreography through a questionnaire survey. This practical study was conducted through an online questionnaire survey among 52 acting choreographers, members of the National Choreographic Union of Ukraine, 92 students of the Faculty of Choreographic Arts of the Kyiv National University of Culture and Arts, and 34 sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…On the other hand, few students win truly international or national competitions (Olympiads), so many other students consider themselves "failures" (Yu & Buck, 2022). Finally, the overemphasis on competition leads university students to gain a narrow awareness of the meaning and role of ballroom dance, as they become focused primarily on meeting the basic criteria of competitions rather than learning about choreography and realizing creativity in a choreographer's life (Bazela et al, 2022). In addition, such students may lose the connection between the acquisition of theoretical and practical skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, few students win truly international or national competitions (Olympiads), so many other students consider themselves "failures" (Yu & Buck, 2022). Finally, the overemphasis on competition leads university students to gain a narrow awareness of the meaning and role of ballroom dance, as they become focused primarily on meeting the basic criteria of competitions rather than learning about choreography and realizing creativity in a choreographer's life (Bazela et al, 2022). In addition, such students may lose the connection between the acquisition of theoretical and practical skills.…”
Section: Discussionmentioning
confidence: 99%
“…A similar issue was addressed by Androshchuk et al (2023), who identified the basics of modern teaching of choreography in higher education institutions of Ukraine. Bazela et al (2022) focused on the main trends in the process of training choreography specialists. Bashkir et al (2022) also turned to similar studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the system of preparation of future choreographers the coexistence of two strategies of training organization: traditional and innovative meets the modern requirements of education (Bazela et al, 2022a). The innovative training influences the formation of many important skills for choreographer, stimulates the creative activity in the process of training, readiness for cooperation in difficult situations, innovative environment contributes to the emergence of personal creativity, development of critical thinking, promotes the revaluation of own abilities (Norton, 2020).…”
Section: Training Of Choreographers In Ukraine: Innovative Challenges...mentioning
confidence: 99%